2020
DOI: 10.24180/ijaws.749512
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activities of Some Wild and Cultivated Edible Mushrooms in Turkey

Abstract: were obtained from different locations in Turkey. Phenylalanine ammonia lyase (PAL) enzyme activity, ascorbate peroxidase (APX), peroxidase (POD), and superoxide dismutase (SOD) activity changes and nitrate, β-carotene and lycopene levels were investigated in 15 samples to determine antioxidant enzyme capacity. As a result of the study, the highest amount of β-carotene and lycopene were determined in H. erinaceus. P. ostreatus-2 had the lowest amount of β-carotene, whereas Pleurotus ostreatus-1 had the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Jayakumar et al [78] determined β-carotene in a 5-fold higher concentration than the present study. Robaszkiewicz et al [79], Jaworska et al [80], and Turfan et al [81] found lycopene presence in addition to β-carotene. The latter was present at a much lower concentration in P. ostreatus.…”
Section: Discussionmentioning
confidence: 98%
“…Jayakumar et al [78] determined β-carotene in a 5-fold higher concentration than the present study. Robaszkiewicz et al [79], Jaworska et al [80], and Turfan et al [81] found lycopene presence in addition to β-carotene. The latter was present at a much lower concentration in P. ostreatus.…”
Section: Discussionmentioning
confidence: 98%